Hydrological and Morphometric Assessment of the Warana River Basin, Maharashtra, India: Informing Irrigation Water Practices in Agricultural Dominant Landscapes - Patil, Suraj Kalgonda; Bhagwat, Tejaswini Nikhil; Sajane, Amitkumar Sukumar; Mulla, Amanulla Liyakatali; Patil, Gomatesh Sharad (Research Advances and Challenges in Agricultural Sciences Vol. 6, 2024)
This research paper delves into the morphometric characteristics of the Warana River basin in Maharashtra, shedding light on its hydrological conditions, particularly in agriculture-dominated areas. Utilizing geo-processing techniques in QGIS 3.16, the study calculates various morphometric parameters to discern the basin's hydrological intricacies. The Warana River basin, identified as a Seventh-order basin, exhibits a dendritic drainage pattern with notable stream frequency (2.99/km), infiltration number (7.22), and drainage density (2.41 km/km2), indicating heightened runoff potential. While a low Constant of channel maintenance (0.41) and lineament density (0.20 km/km2) suggests moderate recharge potential, the interrelationship among morphometric parameters denotes a basin with moderate flood and recharge properties. Flood frequency analysis at the Shigaon River gauging station indicates frequent floods in the basin, and decadal water table fluctuations reveal moderate to high recharge characteristics. The study underscores the significance of morphometric analysis for effective watershed management, advocating the development of surface water harvesting and management plans. For semiarid river basins with moderate groundwater potential and flood propensity, the implementation of surface water storage structures emerges as a practical solution for flood control and groundwater harvesting. Elevated stream frequency and lineament density in the upper reaches of the Warana River basin highlight substantial surface water resources, emphasizing the potential for constructing water conservation and irrigation projects. The fluctuation in pre- and post-monsoon groundwater tables indicates moderate recharge potential, paving the way for the establishment of groundwater recharge structures in the basin's lower southeastern reaches.